A Beginner's Guide for Educators to Use ChatGPT for Teaching and Research - Keng Sheng, Chew; Ernisa, Marzuki; Stephanie, Chua (UNIMAS Publisher, 2025)
From generating assessment questions and creating lesson plans to applying the Feynman Technique, embedding Socratic questioning, role-playing as a viva-voce examiner, and writing problem-based learning triggers, this concise guide offers strategies for effectively using ChatGPT in teaching and learning across various disciplines. It also addresses challenges like AI overreliance and hallucinations, ensuring this artificial intelligence model is used responsibly. Filled with real-world examples, this book inspires educators to use ChatGPT to foster creativity, personalize learning, and prepare students for the future.